Monetary Policy Communications and their Effects on Household Inflation Expectations - Olivier Coibion; Yuriy Gorodnichenko; Michael Weber (Center for Economic Studies and ifo Institute (CESifo), 2019)
We study how different forms of communication influence the inflation expectations of individuals in a randomized controlled trial. We first solicit individuals' inflation expectations in the Nielsen Homescan panel and then provide eight different forms of information regarding inflation. Reading the actual Federal Open Market Committee (FOMC) statement has about the same average effect on expectations as simply being told about the Federal Reserve's inflation target. Reading a news article about the most recent FOMC meetings results in a forecast revision which is smaller by half. Our results have implications for how central banks should communicate to the broader public.
Keywords: E31; C83; D84; 330; expectations management; inflation expectations; surveys; communication; randomized controlled trial